PENERAPAN MODEL PROBLEM BASED LEARNING (PEMBELAJARAN BERBASIS MASALAH) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - F. Kurnia Nirmala Sari (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2022)
This study aims to determine the effect Problem Based Learning model on student’s critical thinking skills. The research methos used is a control group pretest-posttest design that uses the N-Gain test to analiyze data on student’s critical thinking skills. The sample used in this study was obtained by using cluster random sampling technique from the population of grade X SMA Negeri 2 Ngawi. The esperimental class N-Gain test result are 0,68 and are in the medium category, anthe control class has N-Gain value 0f 0,53 and is also is the medium category, but the experimental class N-Gain is treather than the control class, so thah this research can be said that the application of the Problem Based Learning (PBL) learning model has a significant influence on student’s critical thinking skills.